LAPORAN KASUS: LOW GRADE FIBROMYXOID SARCOMA RECURRENT REGIO FEMUR SINISTRA - Anlidya Permatasari Gunawijaya (E-Jurnal Medika Udayana, 2014)
I report a case of 42 years old man who presented with a huge tumor on left thigh thatprogressively growing in 10 months. This patient had history of three times tumorresections and local recurrent, but had not received any other therapy. Physical examinationon left thigh region showed a mass with size 40x20x10 cm, solid, fixed, with ulcers andbleeding. Histological evaluation revealed a cellular lesion consist of spindle cells withatypical fibroblast in collagenous stroma, arranged in plexiform pattern. This patient wasdiagnosed with low grade fibromyxoid sarcoma recurrent regio femur sinistra and treatedwith wide excision.